School-based mental health support for children with English as an additional language - Howard, Katie; Moore, Darren (Frontiers in Education, 2026)
IntroductionOver 20% of school children in England speak English as an additional language (EAL), a figure that is increasing each year. Given an unrelated increase in the prevalence of mental health difficulties among young people, the number of multilingual children in England experiencing mental health difficulties is inevitably on the rise. With growing support in England for mental health services to be embedded into educational settings and delivered by educational mental health practitioners (EMHPs), this article investigates school-based mental health support in England for children with EAL.MethodsFourteen EMHPs who administer low-intensity psychological therapies to EAL pupils in schools were interviewed and data were analysed using a critical realist-orientated thematic analysis.ResultsResults suggest that school-based mental health interventions in England may be less accessible for EAL pupils than their monolingual peers. Along with cultural differences and mental health-related stigma, some aspects of therapy were ‘lost in translation’. This affected both the accessibility and the effectiveness of support in schools, from identification to treatment.DiscussionNavigating multilingualism in therapeutic interventions with young people is complex. Greater linguistic flexibility, including more choice over the language(s) used in psychotherapeutic interventions, is pivotal to improving mental healthcare for children with EAL.